Biochemical changes in lumbar facet joint and disc degeneration by T2 mapping - Ding, Yi; Liu, Liping; Shi, Jiangyou; Zhang, Xiaodong; Chen, Rongchun; Xu, Shuaishuai (BMC musculoskeletal disorders, 2024)
To investigate the biochemical changes in lumbar facet joint (LFJ) and intervertebral disc (IVD) with different degenerative grade by T2* mapping. Sixty-eight patients with low back pain (study group) and 20 volunteers (control group) underwent standard MRI protocols and axial T2* mapping. Morphological evaluation of LFJ and IVD were performed on T2-weighted imaging according to Weishaupt and Pfirrmann grading system, respectively. T2* values of LFJ and of AF (anterior annulus fibrosus), NP (nucleus pulposus), and PF (posterior annulus fibrosus) in IVD were measured. Kruskal-Wallis test and Wilcoxon rank-sum test were used to compare T2* values of subjects with different degenerative grade. The mean T2* value of grade 0 LFJ (21.68[17.77,26.13]) was higher than those of grade I (18.42[15.68,21.8], p < 0.001), grade II (18.98[15.56,22.76], p = 0.011) and grade III (18.38[16.05,25.07], p = 0.575) LFJ in study group, and a moderate correlation was observed between T2* value and LFJ grade (rho=-0.304, p < 0.001) in control group. In the analysis of IVD, a moderate correlation was observed between AF T2* value and IVD grade (rho=-0.323, p < 0.001), and between NP T2* value and IVD grade (rho=-0.328, p < 0.001), while no significant difference was observed between the T2* values of PF in IVD of different grade in study group. Downward trend of T2* values can be found in LFJ, AF and NP as the degenerative grade rised. But in elderly patients with low back pain, no change trend was found in LFJ due to increased fluid accumulation in the joint space.